ANALISIS PERENCANAAN PAJAK ATAS PENYUSUTAN ASET TETAP GUNA MEMPERKECIL PAJAK PENGHASILAN BADAN (Studi Kasus Pada Kopkar PT. Gudang Garam Tbk. Kediri “MEKAR”) - Alvina Wahyu Sukmaningtias; Akhmad Naruli; Khasanah Sahara (Cahaya Ilmu Bangsa, 2025)
Tax planning is the first step in tax management. At this stage, research data is collected on tax regulations so that the type of savings measures that will be implemented can be selected. Kopkar PT. Gudang Garam Tbk, Kediri